Evaluation of receptor‐ligand mechanisms of dual‐targeted particles to an inflamed endothelium. Issue 1 (20th June 2016) - Fromen, Catherine A.; Fish, Margaret B.; Zimmerman, Anthony; Adili, Reheman; Holinstat, Michael; Eniola‐Adefeso, Omolola
Abstract: Vascular‐targeted carriers (VTCs) are designed as leukocyte mimics, decorated with ligands that target leukocyte adhesion molecules (LAMs) and facilitate adhesion to diseased endothelium. VTCs require different design considerations than other targeted particle therapies; adhesion of VTCs in regions with dynamic blood flow requires multiple ligand‐receptor (LR) pairs that provide particle adhesion and disease specificity. Despite the ultimate goal of leukocyte mimicry, the specificity of multiple LAM‐targeted VTCs remains poorly understood, especially in physiological environments. Here, we investigate particle binding to an inflamed mesentery via intravital microscopy using a series of particles with well‐controlled ligand properties. We find that the total number of sites of a single ligand can drive particle adhesion to the endothelium, however, combining ligands that target multiple LR pairs provides a more effective approach. Combining sites of sialyl Lewis A (sLe A ) and anti‐intercellular adhesion molecule‐1 (aICAM), two adhesive molecules, resulted in ∼3–7‐fold increase of adherent particles at the endothelium over single‐ligand particles. At a constant total ligand density, a particle with a ratio of 75% sLe A : 25% aICAM resulted in more than 3‐fold increase over all over other ligand ratios tested in our in vivo model. Combined with in vivo and in silico data, we find the best dual‐ligand design of a particle is heavily dependent on the surface expression of the endothelial cells, producing superior adhesion with more particle ligand for the lesser‐expressed receptor. These results establish the importance of considering LR‐kinetics in intelligent VTC ligand design for future therapeutics.